Preparation method of novel anti-skinning high-temperature-resistant castable
By pretreating corundum powder and combining it with modified carbon fiber, the problem of high-temperature resistant castable is easily cracked and crusted under high temperature conditions, and the high toughness and thermal stability of castable is achieved.
Patent Information
- Application Number
- CN202411557220.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-04
AI Technical Summary
Existing high-temperature resistant castables are prone to cracks and crusts under high temperature conditions, resulting in clogging of the kiln system.
By pretreating the corundum powder, loading melamine, and condensing reaction with the modified carbon fiber, the modified carbon fiber is ordered to load the corundum powder, improving its binding performance with mullite, and connecting the corundum powder with aluminum nitride Carbon fiber, enhances the toughness and thermal stability of the castable.
It effectively reduces thermal stress and cracks caused by temperature changes, prevents crust and fall off, and improves the pressure resistance and thermal stability of the castable material.
Smart Images

Figure BDA0005116837760000061 
Figure BDA0005116837760000071 
Figure BDA0005116837760000072
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of casting material preparation, and in particular to a method for preparing a novel anti-skinning and high-temperature resistant casting material. Background Art
[0002] Castable is a granular or powdery material made of refractory materials with a certain amount of binder. It has high fluidity and is suitable for amorphous refractory materials formed by casting. Compared with other amorphous refractory materials, it has higher binder and moisture content and better fluidity, so amorphous refractory materials have a wider range of applications. The material and binder used can be selected according to the use conditions. It can be directly cast into a lining for use, or it can be made into a prefabricated block by casting or vibration compaction.
[0003] Existing high-temperature resistant castables mostly use corundum as aggregate. Although it has good high-temperature resistance, it has poor thermal stability. Cracks will appear on the surface of the castable during use. In addition, since volatile components such as alkali, chlorine, and sulfur will be produced during the combustion process, these volatile components will repeatedly volatilize and condense under high temperature conditions, causing these volatile components to enter the cracks and condense on the surface of the castable, forming a crust, which will cause the kiln system to be blocked. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a method for preparing a novel anti-skinning and high-temperature resistant castable.
[0005] The technical solution of the present invention is: a method for preparing a novel anti-scaling high-temperature resistant castable, comprising the following steps:
[0006] S1. Take 50-60 parts of mullite, 20-25 parts of corundum powder, 3-8 parts of calcium aluminate cement, 1-3 parts of water reducing agent, 2-5 parts of silica powder and 8-10 parts of modified carbon fiber as raw materials by weight;
[0007] S2, adding corundum powder to ammonia water with a mass concentration of 50-60%, ultrasonically dispersing for 5-10 minutes, adding melamine to the ammonia water, then stirring and heating the ammonia water, gradually adding silane coupling agent to the ammonia water during the heating process, until the ammonia water is heated to 70-80°C, and stopping the heat preservation after 20-25 minutes, waiting for the ammonia water to cool to room temperature, filtering to obtain the pretreated corundum powder; wherein the mass ratio of corundum powder to ammonia water is 1:30-40, the amount of melamine added accounts for 1-3% of the total mass of ammonia water, and the amount of silane coupling agent added accounts for 0.2-0.3% of the total mass of ammonia water;
[0008] S3, loading the modified carbon fiber onto the surface of the pretreated corundum powder to obtain the corundum powder loaded with the modified carbon fiber;
[0009] S4. Add mullite, water reducing agent, silica powder and calcium aluminate cement into a mixer according to the weight parts, stir for 5 to 10 minutes, add corundum powder loaded with modified carbon fiber into the mixer, add water accounting for 15 to 20% of the total mass of the raw materials, stir for 20 to 30 minutes to obtain a casting material.
[0010] Description: The above castable is prepared by pretreating the corundum powder so that melamine is loaded on the corundum powder. The amino group on the melamine can react with the formaldehyde loaded on one end of the modified carbon fiber to load the modified carbon fiber on the corundum powder in an orderly manner, so that the corundum powder can be well combined with the mullite. In addition, due to the high temperature during the use of the castable, melamine can be used as a nitrogen source to react with the alumina in the corundum powder and be converted into aluminum nitride. The corundum powder and the carbon fiber are connected by aluminum nitride, which improves the toughness and thermal stability of the castable, reduces the thermal stress and cracks caused by temperature changes, avoids the expansion of cracks, and prevents the crusting and shedding during the use of the castable.
[0011] Furthermore, in step S1, the water reducing agent is sodium lignin sulfonate or sodium allyl sulfonate.
[0012] Note: The above water reducer can improve the bonding properties of the castable, reduce the porosity and reduce the amount of water used during the mixing process.
[0013] Furthermore, in step S1, the particle size of the corundum powder is 10 to 20 μm.
[0014] Note: Limiting the particle size of the corundum powder can ensure that the corundum powder can fully fill the pores in the mullite and reduce the porosity of the castable.
[0015] Furthermore, in step S1, the length of the modified carbon fiber is 1 to 3 mm.
[0016] Note: Limiting the length of modified carbon fiber can ensure the uniform distribution of carbon fiber and avoid aggregation and entanglement of carbon fiber due to excessive length.
[0017] Furthermore, in step S1, the method for preparing the modified carbon fiber comprises the following steps:
[0018] S1-1, adding carbon fiber into anhydrous ethanol, and ultrasonically dispersing for 5 to 10 minutes to obtain a carbon fiber suspension; wherein the mass ratio of carbon fiber to anhydrous ethanol is 1:30 to 50;
[0019] S1-2, use a sprayer to spray the carbon fiber suspension onto the substrate, the nozzle direction of the sprayer is perpendicular to the substrate, so that the carbon fibers are arranged vertically on the substrate; wherein the spraying amount of the carbon fiber suspension is 50-60 ml / cm 2 ;
[0020] S1-3, hoisting the substrate horizontally and lowering the substrate, so that the carbon fibers on the substrate are immersed in dilute sulfuric acid with a mass concentration of 10-15% and a formaldehyde aqueous solution with a mass concentration of 20-30% successively for modification treatment; wherein the immersion time in the dilute sulfuric acid is 4-5 minutes, and the immersion time in the formaldehyde aqueous solution is 10-15 minutes;
[0021] S1-4, repeat step S1-3 2 to 4 times, and each subsequent immersion time in dilute sulfuric acid is shortened by 30 to 40 seconds compared with the previous time, and the immersion time in the formaldehyde aqueous solution is extended by 1 to 2 minutes compared with the previous time, and then the carbon fiber is scraped off the substrate to obtain modified carbon fiber.
[0022] Description: The modified carbon fiber is sprayed onto a substrate in a unidirectional manner by a spraying method, and then one end of the carbon fiber is alternately immersed in dilute sulfuric acid and a formaldehyde aqueous solution. The dilute sulfuric acid can oxidize the carbon fiber, so that one end of the carbon fiber is loaded with hydroxyl groups. Subsequently, the hydroxyl groups react with formaldehyde to cause one end of the carbon fiber to be loaded with formaldehyde. The dilute sulfuric acid can accelerate the hydroxylation reaction rate of formaldehyde. The immersion time in the dilute sulfuric acid is gradually shortened to avoid excessive oxidation of the carbon fiber and reaction of formaldehyde with the dilute sulfuric acid. The immersion time in the formaldehyde aqueous solution is gradually prolonged to ensure that the carbon fiber is fully loaded with formaldehyde.
[0023] Furthermore, in step S1-2, the distance between the nozzle of the sprayer and the substrate is 20-30 cm, the spraying pressure is 0.2-0.4 MPa, and the spraying speed is 60-100 cm / s.
[0024] Note: Limiting the spraying parameters of the sprayer can ensure that the carbon fibers are arranged vertically on the substrate and avoid the carbon fibers from being entangled.
[0025] Further, in step S3, the method for loading the modified carbon fiber onto the surface of the pretreated corundum powder includes the following steps:
[0026] S3-1, adding the pretreated corundum powder and modified carbon fiber into petroleum ether according to the weight parts, and ultrasonically dispersing for 10 to 15 minutes to obtain a mixed solution; wherein the solid-liquid ratio in the mixed solution is 1:20 to 30;
[0027] S3-2. Use dilute hydrochloric acid with a mass concentration of 10-15% to adjust the pH value of the mixed solution to 4-6, then heat the mixed solution once to increase the temperature of the mixed solution to 70-80°C, and keep it warm for 1-2 hours. After the insulation is completed, heat the mixed solution for a second time to increase the temperature of the mixed solution to 100-110°C, and keep it warm for 2-3 hours, and then filter to obtain the corundum micropowder loaded with modified carbon fiber.
[0028] Note: The above loading method is due to the fact that one end of the carbon fiber is loaded with formaldehyde, and the corundum micropowder is loaded with melamine. Under acidic conditions, the aldehyde group of formaldehyde can undergo a condensation reaction with the amino group of melamine, so that one end of the carbon fiber can be stably loaded on the corundum micropowder.
[0029] Furthermore, the heating rate of the first heating is 10-12°C / min, and the heating rate of the second heating is 3-5°C / min.
[0030] Note: Limiting the heating rates of the primary heating and the secondary heating can ensure that formaldehyde and melamine fully react and solidify, thereby ensuring the bonding strength between the carbon fiber and melamine.
[0031] The beneficial effects of the present invention are:
[0032] (1) The present invention pre-treats the corundum powder so that melamine is loaded on the corundum powder. The amino group on the melamine can undergo a condensation reaction with the formaldehyde loaded on one end of the modified carbon fiber, so that the modified carbon fiber is loaded on the corundum powder in an orderly manner, thereby ensuring that the corundum powder and mullite are well combined, improving the toughness and thermal stability of the castable, reducing the thermal stress and cracks caused by temperature changes, avoiding the expansion of cracks, and preventing the crusting and shedding of the castable during use.
[0033] (2) The present invention sprays the carbon fibers onto a substrate in a unidirectional manner by spraying, and then alternately immerses one end of the carbon fibers in dilute sulfuric acid and a formaldehyde aqueous solution. The dilute sulfuric acid can oxidize the carbon fibers, so that one end of the carbon fibers is loaded with hydroxyl groups. The hydroxyl groups then react with formaldehyde to cause a hydroxylation reaction, so that one end of the carbon fibers is loaded with formaldehyde. DETAILED DESCRIPTION
[0034] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0035] Embodiment 1: A method for preparing a novel anti-skinning high temperature resistant castable, comprising the following steps:
[0036] S1. Take 55 parts of mullite, 22 parts of corundum powder, 5 parts of calcium aluminate cement, 2 parts of water reducer, 4 parts of silicon powder and 9 parts of modified carbon fiber as raw materials by weight; wherein the water reducer is sodium lignin sulfonate, the particle size of the corundum powder is 10-20 μm, and the length of the modified carbon fiber is 2 mm;
[0037] S2, adding corundum powder to ammonia water with a mass concentration of 55%, ultrasonically dispersing for 8 minutes, adding melamine to the ammonia water, then stirring and heating the ammonia water, gradually adding silane coupling agent to the ammonia water during the heating process, until the ammonia water is heated to 75°C, and stopping the heat preservation after 22 minutes, waiting for the ammonia water to cool to room temperature, filtering to obtain the pretreated corundum powder; wherein, the mass ratio of corundum powder to ammonia water is 1:35, the amount of melamine added accounts for 2% of the total mass of ammonia water, the amount of silane coupling agent added accounts for 0.25% of the total mass of ammonia water, and the silane coupling agent uses KH-550;
[0038] S3, loading the modified carbon fiber onto the surface of the pretreated corundum powder to obtain the corundum powder loaded with the modified carbon fiber;
[0039] S4, adding mullite, water reducing agent, silica powder and calcium aluminate cement into a mixer according to the weight parts, stirring for 8 minutes, adding corundum powder loaded with modified carbon fiber into the mixer, adding water accounting for 18% of the total mass of the raw materials, stirring for 25 minutes to obtain a casting material;
[0040] The preparation method of modified carbon fiber comprises the following steps:
[0041] S1-1, adding carbon fiber into anhydrous ethanol, and ultrasonically dispersing for 8 minutes to obtain a carbon fiber suspension; wherein the mass ratio of carbon fiber to anhydrous ethanol is 1:40;
[0042] S1-2, use a sprayer to spray the carbon fiber suspension onto the substrate, the nozzle direction of the sprayer is perpendicular to the substrate, so that the carbon fibers are arranged vertically on the substrate; wherein the spraying amount of the carbon fiber suspension is 55ml / cm 2 ; Among them, the distance between the nozzle of the sprayer and the substrate is 25cm, the spraying pressure is 0.3MPa, and the spraying speed is 80cm / s;
[0043] S1-3, hoisting the substrate horizontally and lowering the substrate, so that the carbon fibers on the substrate are immersed in dilute sulfuric acid with a mass concentration of 12% and a formaldehyde aqueous solution with a mass concentration of 25% for modification treatment; wherein the immersion time in the dilute sulfuric acid is 4.5 minutes, and the immersion time in the formaldehyde aqueous solution is 13 minutes;
[0044] S1-4, repeating step S1-3 three times, and each subsequent immersion time in dilute sulfuric acid is shortened by 35 seconds compared with the previous time, and the immersion time in the formaldehyde aqueous solution is extended by 1.5 minutes compared with the previous time, and then scraping the carbon fiber off the substrate to obtain modified carbon fiber;
[0045] In step S3, the method for loading the modified carbon fiber onto the surface of the pretreated corundum powder comprises the following steps:
[0046] S3-1, adding the pretreated corundum powder and modified carbon fiber into petroleum ether according to the weight parts, and ultrasonically dispersing for 13 minutes to obtain a mixed solution; wherein the solid-liquid ratio in the mixed solution is 1:25;
[0047] S3-2. Use dilute hydrochloric acid with a mass concentration of 12% to adjust the pH value of the mixed solution to 5, then heat the mixed solution once to increase the temperature of the mixed solution to 75°C, and keep it warm for 1.5 hours. After the insulation is completed, heat the mixed solution for a second time to increase the temperature of the mixed solution to 105°C, and keep it warm for 2.5 hours. Then filter to obtain the corundum micropowder loaded with modified carbon fiber; the heating rate of the first heating is 11°C / min, and the heating rate of the second heating is 4°C / min.
[0048] Example 2: This example is basically the same as Example 1, except that 50 parts of mullite, 20 parts of corundum powder, 3 parts of calcium aluminate cement, 1 part of water reducer, 2 parts of silicon powder, and 8 parts of modified carbon fiber are selected as raw materials by weight.
[0049] Example 3: This example is basically the same as Example 1, except that 60 parts of mullite, 25 parts of corundum powder, 8 parts of calcium aluminate cement, 3 parts of water reducer, 5 parts of silicon powder, and 10 parts of modified carbon fiber are selected as raw materials by weight.
[0050] Example 4: This example is basically the same as Example 1, except that the added amount of melamine accounts for 1% of the total mass of the ammonia water.
[0051] Example 5: This example is basically the same as Example 1, except that the added amount of melamine accounts for 3% of the total mass of ammonia water.
[0052] Example 6: This example is basically the same as Example 1, except that the added amount of the silane coupling agent accounts for 0.2% of the total mass of the ammonia water.
[0053] Example 7: This example is basically the same as Example 1, except that the added amount of the silane coupling agent accounts for 0.3% of the total mass of the ammonia water.
[0054] Example 8: This example is basically the same as Example 1, except that the carbon fibers on the substrate are successively immersed in a dilute sulfuric acid solution with a mass concentration of 10% and a formaldehyde aqueous solution with a mass concentration of 20% for modification.
[0055] Example 9: This example is basically the same as Example 1, except that the carbon fibers on the substrate are successively immersed in a dilute sulfuric acid solution with a mass concentration of 15% and a formaldehyde aqueous solution with a mass concentration of 30% for modification.
[0056] Example 10: This example is basically the same as Example 1, except that step S1-3 is repeated twice.
[0057] Example 11: This example is basically the same as Example 1, except that step S1-3 is repeated 4 times.
[0058] Example 12: This example is basically the same as Example 1, except that each subsequent immersion time in dilute sulfuric acid is shortened by 30 seconds compared with the previous time, and the immersion time in the formaldehyde aqueous solution is extended by 1 minute compared with the previous time.
[0059] Example 13: This example is basically the same as Example 1, except that each subsequent immersion time in dilute sulfuric acid is shortened by 40 seconds compared with the previous time, and the immersion time in the formaldehyde aqueous solution is extended by 2 minutes compared with the previous time.
[0060] Example 14: This example is basically the same as Example 1, except that the mixed liquid is heated once to raise the temperature of the mixed liquid to 70°C and kept warm for 1 hour.
[0061] Example 15: This example is basically the same as Example 1, except that the mixed liquid is heated once to raise the temperature of the mixed liquid to 80°C and kept warm for 2 hours.
[0062] Example 16: This example is basically the same as Example 1, except that after the insulation is completed, the mixed liquid is heated for a second time to raise the temperature of the mixed liquid to 100°C and keep it warm for 2 hours.
[0063] Example 17: This example is basically the same as Example 1, except that after the insulation is completed, the mixed liquid is heated for a second time to raise the temperature of the mixed liquid to 110°C and keep it warm for 3 hours.
[0064] Comparative Example 1: Taking Example 1 as a reference, the modified carbon fiber was replaced with unmodified carbon fiber.
[0065] Comparative Example 2: Using Example 1 as a reference, the corundum powder was not pretreated.
[0066] Comparative Example 3: With reference to Example 1, the immersion time in the dilute sulfuric acid and the immersion time in the formaldehyde aqueous solution did not change.
[0067] Comparative Example 4: Using Example 1 as a reference, the temperature of the mixed solution was directly raised to 105° C. and kept warm for 2.5 h.
[0068] Experimental example: In order to explore the influence of the parameters of each embodiment on the performance of the castable, the castables prepared in each embodiment were made into test blocks, which were then calcined at 1550°C for 3h, and the performance of each test block was tested. The specific exploration is as follows:
[0069] Experimental Example 1: Investigating the influence of castable composition on castable performance
[0070] Using Examples 1 to 3 and Comparative Example 1 as experimental comparisons, the castable properties under different compositions are shown in Table 1 below:
[0071] Table 1 Castable properties under different compositions
[0072] Group Compressive strength / MPa Line change rate after burning / % Example 1 65.5 -0.12 Example 2 62.3 -0.17 Example 3 63.7 -0.14 Comparative Example 1 54.3 -0.29
[0073] It can be seen from the data in Table 1 that compared with Examples 1, 2, and 3, the castable of Example 1 has the highest compressive strength and the smallest linear change rate after firing, indicating that the castable of Example 1 has the highest strength and the best thermal stability. Therefore, the castable composition selected in Example 1 is optimal.
[0074] Compared with Comparative Example 1, after using unmodified carbon fiber, the compressive strength of the castable decreases and the linear change rate after firing increases. This may be because the modified carbon fiber is more evenly distributed and has the best bonding performance with mullite. Therefore, the modified carbon fiber selected in Example 1 is better as a principle.
[0075] Experimental Example 2: Effect of pretreatment parameters of corundum powder on castable properties
[0076] Using Example 1, Examples 4 to 7, and Comparative Example 2 as experimental comparisons, the castable properties of the corundum powder under different pretreatment parameters are shown in Table 2 below:
[0077] Table 2 Castable properties under different pretreatment parameters of corundum powder
[0078]
[0079]
[0080] It can be seen from the data in Table 2 that, compared with Examples 1, 4, and 5, as the amount of melamine added increases, the compressive strength of the castable gradually increases, and the rate of change of the line after burning gradually decreases, until the compressive strength of Example 1 reaches the highest and the rate of change of the line after burning is the smallest. As the amount of melamine added continues to increase, the compressive strength and the rate of change of the line after burning of the castable begin to have no obvious changes. This may be because the melamine that can be loaded on the corundum micropowder has reached the maximum value. Therefore, from a cost perspective, the amount of melamine added selected in Example 1 is optimal.
[0081] Compared with Examples 1, 6, and 7, the castable of Example 1 has the highest compressive strength and the smallest linear change rate after firing, indicating that the castable of Example 1 has the highest strength and the best thermal stability. This may be because too much silane coupling agent causes too much coupling agent layer to form on the surface of the corundum particles, affecting the bonding performance between melamine and corundum powder. Therefore, the amount of silane coupling agent added selected in Example 1 is optimal.
[0082] Compared with Comparative Example 2, in Example 1, after the corundum micropowder is not pretreated, the compressive strength of the castable decreases and the linear change rate after firing increases. This may be because the surface of the corundum micropowder cannot fully and orderly load the carbon fiber without pretreatment of the corundum micropowder, and the bonding performance between the corundum micropowder and the carbon fiber deteriorates. Therefore, the corundum micropowder pretreatment method selected in Example 1 is better.
[0083] Experimental Example 3: Investigating the influence of modified carbon fiber preparation parameters on castable properties
[0084] Using Example 1, Examples 8 to 13, and Comparative Example 3 as experimental comparisons, the castable properties of the modified carbon fiber under different preparation parameters are shown in Table 3 below:
[0085] Table 3 Castable properties under different pretreatment parameters of corundum powder
[0086]
[0087]
[0088] It can be seen from the data in Table 3 that compared with Examples 1, 8, and 9, the castable of Example 1 has the highest compressive strength and the smallest linear change rate after firing, indicating that the castable of Example 1 has the highest strength and the best thermal stability. This may be because the formaldehyde loaded on the surface of the carbon fiber is the most under the concentrations of dilute sulfuric acid and formaldehyde aqueous solution in Example 1, so the concentrations of dilute sulfuric acid and formaldehyde aqueous solution selected in Example 1 are optimal;
[0089] Compared with Examples 1, 10, and 11, the castable of Example 1 has the highest compressive strength and the smallest linear change rate after firing, indicating that the castable of Example 1 has the highest strength and the best thermal stability. This may be because the modification effect of the carbon fiber is the best under the number of repetitions of steps S1-3 selected in Example 1, so the number of repetitions of steps S1-3 selected in Example 1 is optimal;
[0090] Compared with Examples 1, 12, and 13, the castable of Example 1 has the highest compressive strength and the smallest linear change rate after firing, indicating that the castable of Example 1 has the highest strength and the best thermal stability, which may be because the immersion time of dilute sulfuric acid and formaldehyde aqueous solution selected in Example 1 is optimal;
[0091] Compared with Comparative Example 3, when the immersion time in dilute sulfuric acid and the immersion time in formaldehyde aqueous solution remain unchanged, the compressive strength of the castable decreases and the line change rate after firing increases. This may be because immersion in dilute sulfuric acid for too long will cause excessive oxidation of carbon fiber. Therefore, the modification method selected in Example 1 is the best.
[0092] Experimental Example 4: Investigating the effect of temperature when modified carbon fiber is loaded onto pretreated corundum powder on the properties of the castable
[0093] Using Example 1, Examples 14 to 17, and Comparative Example 4 as experimental comparisons, the castable properties at different temperatures when the modified carbon fiber is loaded onto the pretreated corundum powder are shown in Table 4 below:
[0094] Table 4 Casting material properties at different temperatures when modified carbon fiber is loaded onto pretreated corundum powder
[0095] Group Compressive strength / MPa Line change rate after burning / % Example 1 65.5 -0.12 Embodiment 14 64.2 -0.14 Embodiment 15 63.4 -0.16 Example 16 62.7 -0.19 Embodiment 17 61.3 -0.21 Comparative Example 4 60.1 -0.23
[0096] It can be seen from the data in Table 4 that compared with Examples 1, 14, 15, 16, and 17, both the primary heating parameters and the secondary heating parameters will affect the performance of the castables. Among them, the castable of Example 1 has the highest compressive strength and the smallest linear change rate after burning, indicating that the castable of Example 1 has the highest strength and the best thermal stability. This may be because the binding between the corundum powder and the modified carbon fiber is the best under the primary heating parameters and the secondary heating parameters selected in Example 1. Therefore, the primary heating parameters and the secondary heating parameters selected in Example 1 are both optimal;
[0097] Compared with Comparative Example 4, in Example 1, after the temperature of the mixed solution is directly increased to 105°C, the compressive strength of the castable decreases and the linear change rate after firing increases. This may be because direct heating causes formaldehyde and melamine to fail to fully react. Therefore, the heating method selected in Example 1 is optimal.
Claims
1. A method for preparing a novel anti-skinning high temperature resistant castable, characterized in that: The following steps are involved: S1. Take 50-60 parts of mullite, 20-25 parts of corundum powder, 3-8 parts of calcium aluminate cement, 1-3 parts of water reducing agent, 2-5 parts of silica powder and 8-10 parts of modified carbon fiber as raw materials by weight; S2, adding corundum powder to ammonia water with a mass concentration of 50-60%, ultrasonically dispersing for 5-10 minutes, adding melamine to the ammonia water, then stirring and heating the ammonia water, gradually adding silane coupling agent to the ammonia water during the heating process, until the ammonia water is heated to 70-80°C, and stopping the heat preservation after 20-25 minutes, waiting for the ammonia water to cool to room temperature, filtering to obtain the pretreated corundum powder; wherein the mass ratio of corundum powder to ammonia water is 1:30-40, the amount of melamine added accounts for 1-3% of the total mass of ammonia water, and the amount of silane coupling agent added accounts for 0.2-0.3% of the total mass of ammonia water; S3, loading the modified carbon fiber onto the surface of the pretreated corundum powder to obtain the corundum powder loaded with the modified carbon fiber; S4. Add mullite, water reducing agent, silica powder and calcium aluminate cement into a mixer according to the weight parts, stir for 5 to 10 minutes, add corundum powder loaded with modified carbon fiber into the mixer, add water accounting for 15 to 20% of the total mass of the raw materials, stir for 20 to 30 minutes to obtain a casting material.
2. The method for preparing the novel anti-skinning high temperature resistant castable according to claim 1, characterized in that: In step S1, the water reducing agent is sodium lignin sulfonate or sodium allyl sulfonate.
3. The method for preparing the novel anti-skinning high temperature resistant castable according to claim 1, characterized in that: In step S1, the particle size of the corundum powder is 10 to 20 μm.
4. The method for preparing the novel anti-skinning high temperature resistant castable according to claim 1, characterized in that: In step S1, the length of the modified carbon fiber is 1 to 3 mm.
5. The method for preparing the novel anti-skinning high temperature resistant castable according to claim 1, characterized in that: In step S1, the method for preparing the modified carbon fiber comprises the following steps: S1-1, adding carbon fiber into anhydrous ethanol, and ultrasonically dispersing for 5 to 10 minutes to obtain a carbon fiber suspension; wherein the mass ratio of carbon fiber to anhydrous ethanol is 1:30 to 50; S1-2, use a sprayer to spray the carbon fiber suspension onto the substrate, the nozzle direction of the sprayer is perpendicular to the substrate, so that the carbon fibers are arranged vertically on the substrate; wherein the spraying amount of the carbon fiber suspension is 50-60 ml / cm 2 ; S1-3, hoisting the substrate horizontally and lowering the substrate, so that the carbon fibers on the substrate are immersed in dilute sulfuric acid with a mass concentration of 10-15% and a formaldehyde aqueous solution with a mass concentration of 20-30% successively for modification treatment; wherein the immersion time in the dilute sulfuric acid is 4-5 minutes, and the immersion time in the formaldehyde aqueous solution is 10-15 minutes; S1-4, repeat step S1-3 2 to 4 times, and each subsequent immersion time in dilute sulfuric acid is shortened by 30 to 40 seconds compared with the previous time, and the immersion time in the formaldehyde aqueous solution is extended by 1 to 2 minutes compared with the previous time, and then the carbon fiber is scraped off the substrate to obtain modified carbon fiber.
6. The method for preparing the novel anti-skinning high temperature resistant castable according to claim 5, characterized in that: In step S1-2, the distance between the nozzle of the sprayer and the substrate is 20-30 cm, the spraying pressure is 0.2-0.4 MPa, and the spraying speed is 60-100 cm / s.
7. The method for preparing the novel anti-skinning high temperature resistant castable according to claim 1, characterized in that: In step S3, the method for loading the modified carbon fiber onto the surface of the pretreated corundum powder comprises the following steps: S3-1, adding the pretreated corundum powder and modified carbon fiber into petroleum ether according to the weight parts, and ultrasonically dispersing for 10 to 15 minutes to obtain a mixed solution; wherein the solid-liquid ratio in the mixed solution is 1:20 to 30; S3-2. Use dilute hydrochloric acid with a mass concentration of 10-15% to adjust the pH value of the mixed solution to 4-6, then heat the mixed solution once to increase the temperature of the mixed solution to 70-80°C, and keep it warm for 1-2 hours. After the insulation is completed, heat the mixed solution for a second time to increase the temperature of the mixed solution to 100-110°C, and keep it warm for 2-3 hours, and then filter to obtain the corundum micropowder loaded with modified carbon fiber.
8. The method for preparing the novel anti-skinning high temperature resistant castable according to claim 7, characterized in that: The heating rate of the first heating is 10-12°C / min, and the heating rate of the second heating is 3-5°C / min.
Citation Information
Patent Citations
Mullite composite castable with enhanced anti-seismic property and preparation method of mullite composite castable
CN117567140A
Composite corundum wear-resistant plastic refractory used for CFB target region and preparation method of composite corundum wear-resistant plastic refractory
CN118619690A
Preparation method of aluminum nitride powder and aluminum nitride powder
CN118878334A
Carbon foam, complex, and production method
WO2020045645A1